The integrity of cholinergic basal forebrain neurons depends on expression of Nkx2-1 - Magno, Lorenza; Kretz, Oliver; Bert, Bettina; Ersözlü, Sara; Vogt, Johannes; Fink, Heidrun; Kimura, Shioko; Vogt, Angelika; Monyer, Hannah; Nitsch, Robert; Naumann, Thomas (European journal of neuroscience, 2011)
The transcription factor Nkx2-1 belongs to the homeobox-encoding family of proteins that have essential functions in prenatal brain development. Nkx2-1 is required for the specification of cortical interneurons and several neuronal subtypes of the ventral forebrain. Moreover, this transcription factor is involved in migratory processes by regulating the expression of guidance molecules. Interestingly, Nkx2-1 expression was recently detected in the mouse brain at postnatal stages. Using two transgenic mouse lines that allow prenatal or postnatal cell type-specific deletion of Nkx2-1, we show that continuous expression of the transcription factor is essential for the maturation and maintenance of cholinergic basal forebrain neurons in mice. Notably, prenatal deletion of Nkx2-1 in GAD67-expressing neurons leads to a nearly complete loss of cholinergic neurons and parvalbumin-containing GABAergic neurons in the basal forebrain. We also show that postnatal mutation of Nkx2-1 in choline acetyltransferase-expressing cells causes a striking reduction in their number. These degenerative changes are accompanied by partial denervation of their target structures and results in a discrete impairment of spatial memory.
Gesehen am 25.11.2022